Ketahanan Asam Lemak Tidak Jenuh dalam Crude Palm Oil Terproteksi terhadap Aktivitas Mikrob Rumen Domba in Vitro - N C Tiven; L M Yusiati; Rusman Rusman; U Santoso (Media Peternakan, 2011)
The experiment was aimed to study the composition of unsaturated fatty acid, fermentation parameter and microbial activity in the rumen-buffer mixture when protected CPO with casein and formaldehyde was incubated in the in vitro fermentation. CPO and milk powder (1:2) were mixed, added technical formaldehyde 0%, 1%, 2%, and 3% by weight of blend, mixed again to form CCPO. The amount of 0% (0 mg), 1.5% (4.5 mg), 3% (9 mg), 4.5% (13.5 mg) and 6% (18 mg) CCPO was inserted into fermenter bottles containing napier grass and rice bran (60:40), was tested in vitro. The data were analyzed by completely randomized design with factorial pattern 4 x 5 (level of formaldehyde as factor A and level of CPO as factor B). The different of treatments were tested by Duncan's new multiple range test.  Result shows that the increase of formaldehyde level could increase unsaturated fatty acids content, CMC-ase activity, microbial protein and number of protozoa, but decreased NH3, VFA, and pH of rumen fluid. The increase of CPO level also increased fatty acid composition and microbial protein, but decreased NH3, VFA, and pH, CMC-ase activity and number of protozoa in rumen fluid. It can be concluded that encapsulated CPO with formaldehyde increased unsaturated fatty acid composition and microbial activity, but decreased fermentation parameters.